1982
DOI: 10.1111/j.1365-2621.1982.tb12701.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Enteropathogenic Escherichia coli in Camembert Cheese Made From Ultrafiltered Milk

Abstract: Skimmilk retentates from ultrafiltration (UF) were used in combination with concentrated cream (67% milk fat) to prepare a liquid precheese mixture that with the addition of rennet, lactic starter culture and a mold spore preparation of Penicillium candidum was transformed readily into Camembert cheese upon ripening. Yield increases from the retention of soluble milk protein, closer weight control tolerances for individual cheeses and reduction in rennet in comparison to the conventional Camembert process were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
1
4
0
2
Order By: Relevance
“…This confirms the results of other authors who have shown that E. coli was one of the most resistant species within Enterobacteriaceae during ripening of cheeses [47]. Generally, Salmonella is not detected in long-time ripened pressed cheeses with low pH, as in our case [18].…”
Section: Discussionsupporting
confidence: 93%
“…This confirms the results of other authors who have shown that E. coli was one of the most resistant species within Enterobacteriaceae during ripening of cheeses [47]. Generally, Salmonella is not detected in long-time ripened pressed cheeses with low pH, as in our case [18].…”
Section: Discussionsupporting
confidence: 93%
“…However, high buffering capacity of food products had been found to offer protection to microbial cells. For example, Rash and Kosikowski (1982), in their study of certain enteropathogenic bacteria such as E. coli growth in ultrafiltered milk, reported that the increased buffering capacity of the milk provides a good environment for the growth and survival of the bacteria. Misty and Kosikowski (1986) also reported a minimized bacterial cell damage of lactic acid bacteria when growth was studied in a highly concentrated ultrafiltered skim milk, which they attributed to the high buffering capacity of the milk which maintains the pH at high levels for long period.…”
Section: Discussionmentioning
confidence: 98%
“…For the manufacture of Camembert cheese made from pre-cheese, mineral composition has to be appropriate to obtain acid pH by the use of selected bacterial cultures in optimal buffering capacity conditions (Mistry & Maubois, 2004;Rash & Kosikowski, 1982).…”
Section: Influence Of Buffering Capacity On Enzymatic Activities and mentioning
confidence: 99%